2023
DOI: 10.1002/app.54529
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ablation resistance of carbon/phenolic composites based on mesophase pitch reinforced particles

Yaoqun Yue,
Yisen Huang,
Huawei Zou
et al.

Abstract: Phenolic resin (PR)‐based composites are the main materials used in thermal protection system (TPS) at present. However, the low graphitization degree of the char layer formed by PR easily leads to cracks and other defects. In this study, carbon/phenolic composites were modified by mesophase pitch (MP) to improve the structural strength, fracture toughness and crack propagation resistance. The ablation rate was significantly decreased after MP modification compared with the blank sample. With the increase of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…For example, Chang et al reported an Al 2 O 3f -CF/Ph modified with HfB 2 and SiB 6 that achieves a linear ablation rate (LAR) of 0.06 mm/s [21]. Yue et al fabricated a mesophase pitchmodified CF/Ph, and its LAR was as low as 0.0082 mm/s [22]. In our previous work, MoSi 2 and B 4 C were incorporated into CF/Ph to develop a new ceramizable composite exhibiting satisfactory ablation resistance with an LAR of 0.013 mm/s [20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chang et al reported an Al 2 O 3f -CF/Ph modified with HfB 2 and SiB 6 that achieves a linear ablation rate (LAR) of 0.06 mm/s [21]. Yue et al fabricated a mesophase pitchmodified CF/Ph, and its LAR was as low as 0.0082 mm/s [22]. In our previous work, MoSi 2 and B 4 C were incorporated into CF/Ph to develop a new ceramizable composite exhibiting satisfactory ablation resistance with an LAR of 0.013 mm/s [20].…”
Section: Introductionmentioning
confidence: 99%